Changes in Neonatal Mineral Administration and Contaminant Exposure due to Sodium Phosphate Shortage - Porcelli, Peter J.; Holmes, Amy (American Journal of Perinatology, 2017)
Background National pharmaceutical shortages continue to affect clinical patient care, including neonatal patients. Early postnatal nutrition influences health and growth of infants; quantitative reports describing specific effects of drug shortages on neonatal care are not common.Methods Parenteral nutrition (PN) orders created during the study period were modified to adjust for sodium phosphate unavailability. Original PN orders were collected retrospectively and compared with the modified orders for daily mineral doses, calcium:phosphorus ratio, and potential aluminum exposure. The corrected phosphorus dose was determined to compensate for algorithm-driven changes in phosphorus administration.Results The PN corrected phosphorus dose decreased from 58.9 ± 19.7 mg/kg/day to 42.7 ± 21.7 mg/kg/day (mean ± standard deviation [SD], n = 226 from 22 patients, range, 0–63.4 mg/kg/day, p < 0.05) below the minimal recommended daily dose. There was a coincident doubling of the calcium:phosphorus ratio to > 2.5:1, which was above the desired ratio of 1.8:1. Using potassium phosphate as the only intravenous phosphate source increased the potential aluminum exposure to 60% (9.6 ± 5.0) above the recommended Food And Drug Administration (FDA) limit.Discussion Neonatal PN phosphate administration decreased during the sodium phosphate shortage, raised calcium:phosphate ratios, and increased the potential aluminum exposure. Drug shortages continue to affect preterm infants. Coordinated efforts of health professionals with administrative resources are needed to provide effective short-term solutions and develop long-term strategies.Clinical Relevance Providing optimal PN to neonates is essential for postnatal health and growth. This report describes the effect of a national drug shortage of injectable sodium phosphate on PN composition and infant mineral administration.
Keywords: neonate; parenteral nutrition; sodium phosphate; drug shortage; calcium; phosphate